2018
DOI: 10.1155/2018/8591015
|View full text |Cite
|
Sign up to set email alerts
|

Viability of Molds and Bacteria in Tempeh Processed with Supercritical Carbon Dioxides during Storage

Abstract: Application of supercritical carbon dioxide for processing of food products has an impact on microbial inactivation and food quality. This technique is used to preserve tempeh due to no heat involved. The quality of tempeh is highly influenced by mold growth because of its role in forming a compact texture, white color, and functional properties as well as consumer acceptance. This study aims to observe viability of molds and bacteria in tempeh after processed with supercritical CO2 and to determine the best p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
(19 reference statements)
1
6
0
2
Order By: Relevance
“…A similar finding reported that the fat content of Nila tilapia was not affected by scCO 2 from 80 to 90 bars at 40°C [29]. On the contrary, fat content in tempeh reduced at 1100 psi at 31°C [30]. Fat in foods is lipophilic and soluble in supercritical CO 2 ; therefore, it decreased during HPCD processing.…”
Section: Effect Of High-pressure Treatment On Basic Nutrientssupporting
confidence: 69%
See 1 more Smart Citation
“…A similar finding reported that the fat content of Nila tilapia was not affected by scCO 2 from 80 to 90 bars at 40°C [29]. On the contrary, fat content in tempeh reduced at 1100 psi at 31°C [30]. Fat in foods is lipophilic and soluble in supercritical CO 2 ; therefore, it decreased during HPCD processing.…”
Section: Effect Of High-pressure Treatment On Basic Nutrientssupporting
confidence: 69%
“…In contrast, the number of microbes in tilapia decreased by 2 log cycles at a pressure treatment of 80 bar reported by Sugiharto et al [29]. Meanwhile, Kustyawati et al [30] found that tempeh treated with 900 psi significantly (p ≤ 0.05) reduced the number of microbes by 2 logs. e type and chemical contents of products processed with supercritical CO 2 could be the reason for inhibiting microbiological inactivation in treated shrimps in this study.…”
Section: Microbiological Analysismentioning
confidence: 87%
“…Meanwhile, for the overall compactness of the samples, both treatment and control showed compact results with very tight mycelium so that the soybean seeds condensed to have an appearance like tempeh. These results indicate that all samples exhibit the ideal characteristics of tempeh, which have evenly distributed white mycelium with a compact appearance (Kustyawati et al, 2018).…”
Section: Macroscopic Observations During Fermentationmentioning
confidence: 65%
“…Tempeh, in the form of a cylinder with a diameter of 35 mm and a length of 100 mm, fermented for 36 hours at 30 °C, was obtained from the Center of Home Industry Tempeh Making Palembang, Indonesia, placed in a cooler box and carried to the laboratory for direct processing (Kustyawati et al, 2018).…”
Section: Materials and Methodology Treatment Of Tempeh With Supercritical Co2mentioning
confidence: 99%